Molecular epidemiology, associated risk factors, and phylogenetic analysis of anaplasmosis in camel. (October 2018) - Azmat, M.; Ijaz, M.; Farooqi, S.H.; Ghaffar, A.; Ali, A.; Masud, A.; Saleem, S.; Rehman, A.; Ali, M.M.; Mehmood, K.; Khan, Amjad; Zhang, H.
Abstract: Camel Anaplasmosis is caused by members of family Anaplasmatacae, a tick transmitted, obligate intracellular bacteria. The etiological bacteria are transmitted by ixodid tick species. The species have multi host range distribution that is why it is crucial to diagnose it timely. The aim of present study was to investigate the molecular epidemiology i.e. prevalence and risk factors analysis of camel anaplasmosis. Furthermore, variations in hematological standards were also evaluated. The study found an overall 13.33% prevalence in camels. The confirmation of PCR positive samples for Anaplasma spp. was made through sequencing, the study isolatesshowed high homology with Iranian, Chinese, Philippines and South African isolates of Anaplasmatacae (Accession numbers'; KX765882, KP062964, KY242456, LC007100 and U54806) on BLAST queries. The phylogenetic analysis revealedthree study isolates of present study clustered with each other and the cluster was found closer to Chinese isolate of A. phagocytophilum (KY242456), A. marginale (KU586048), and Mongolian isolates of A. ovis (LC194134). Two of the isolates resembled Iranian isolate of Candidatus Anaplasmacamelii (KX765882), while one isolate resembled with Chinese isolates of A. Platys (KX987336) and Croatian isolates of A. Platys (KY114935). The key risk factors odds ratio (OR>1) identified for occurrence of camel anaplasmosis using regression model found sex and age of animal, previous tick history, tick infestation and tick control status, housing type, cracks in walls, rearing system and other species in surrounding as the key risk factors. The hematological parameters like lymphocytes, monocytes, granulocytes and platelets count were significantly decreased ( p  < 0.05) in diseased camels than healthy. This is the first ever molecular data on camel anaplasmosis in Pakistan. The disease should be monitored unceasingly as the etiologies have multi host distribution. Prompt attention should be offered to animals because neutropenia, lymphopenia and thrombocytopenia can exacerbate the disease by making the animal predisposed to otherdiseases. Highlights: Members of  Anaplasmatacae, vector borne pathogens cause camel anaplasmosis. These pathogens are important because of multi host range distribution. Camels of Pakistan were found to harbor multiple species of this family. Sex, age, housing type, tick infestation, previous tick history and tick control status are the main determinants of camel anaplasmosis. The hematological standards like DLC and TLC are significantly distinct among diseased and healthy animals.